Different behavior of human gingival fibroblasts on surface modified zirconia: A comparison between ultraviolet (UV) light and plasma - ZHOU, Jianfeng; TAN, Jianguo; ZHENG, Miao; LIAO, Yu; YANG, Yang; LI, Heping (Dental Materials Journal, 2019)
This study was to evaluate whether UV light irradiation and He plasma treatment of zirconia disks enhances its biocompatibility with human gingival fibroblasts (HGFs), and to compare the difference of two methods. Zirconia disks were prepared and divided into three groups: UVC light treatment (Group UV), He plasma (Group P), and control group. The surface morphology, wettability were analyzed. The cultured HGFs’ adhesive density, morphology, proliferation and collagen synthesis were measured. After UV light and plasma treatment, contact angles decreased. HGFs’ adhesion and proliferation in Group P was the highest (p<0.05) at each time point. HGFs on Group P also released the highest level of Col-1 after 3 and 7 days. Our study demonstrated that plasma and UV light treatment on smooth zirconia improved the hydrophilic property of surface in different mechanism and He plasma had the better effect on cells adhesion, proliferation, and especially on collagen synthesis.